Analysis of Pelvic Bone of Ovariectomized Rats using Infrared and Raman Spectroscopies - Fitriyawardhani, Nurwentari Dyah; Juwono, Ariadne Lakshmidevi; Mulyaningsih, Neng Nenden (UI Scholars Hub, 2022)
Osteoporosis is a bone disease that generally occurs in postmenopausal women. Osteoporosis can be studied using an animal model such as rats because rat bone structure is similar to human bone structure. This research aimed to analyze pelvic bones of ovariectomized rats that showed osteoporosis signs for the first time. In this study, 20 Rattus norvegicus were given ovariectomy at 12 weeks of age and were used as an animal model for menopausal women. The rats were euthanized every 2 weeks from 13 to 21 weeks of age. In addition, the pelvic bones of ovariectomized rats will be analyzed using FTIR and Raman spectroscopy to show the first osteoporosis signs periodically. Results of FTIR and Raman spectroscopy indicated that the pelvic bones of the ovariectomized rats showed the first osteoporosis signs at 17 weeks of age with changes in phosphate and carbonate contents, increased hydroxyl functional groups, reduction of mineral maturity about 7.47%, and reduction of crystallinity about 29.26%. In addition, morphological changes from fine fibers to coarser fibers and reduction of the crystal size and crystallinity index at the angle of 2θ ≅ 25° about 9.29% and 25.18%, respectively, were observed using SEM-EDS and XRD.